Ngo, une petite ville du Nord-Congo : cadre de vie et rôle régional - Damase Ngouma; Pépin Hippolyte Ndey Ngandzo; Robert Ngomeka (Études Caribéennes)
Located in the Plateaux Batéké department, 250 km north of Brazzaville, the town of Ngo is built on the national road n° 2, at the crossroads of four dynamic roads. Organized in an urban community in 2010 and endowed with notable infrastructure and services, it has become a small, cosmopolitan and growing city. The urban landscape has changed over the years and the population has almost doubled between 1996 and 2007, from 3887 to 7500. The administrative advantages of the city and its particular geographical location allow it to maintain socio-economic relations diverse, not only with the 74 villages it borders, but also with Brazzaville, the capital of the country. Its zone of influence extends to the geographical limits of the sub-prefecture of which it is the chief town